Fatores associados à ansiedade, depressão e estresse em professores da Universidade Federal do Ceará durante a terceira onda da pandemia da COVID-19 - Bandeira, Marcos Fábio Pinto (2023)
The COVID-19 pandemic has had a major impact on the world, including the education sector, which has undergone rapid and profound changes. Schools and higher education institutions (HEIs) were directly affected by the suspension of face-to-face classes and their replacement by remote teaching. The objective of this research was to estimate the prevalence of anxiety, depression and stress and associated work factors in professors at the Federal University of Ceará during the third wave of the COVID-19 pandemic. The study is analytical cross-sectional and was carried out between March and July 2022. Teachers responded to an online questionnaire sent by email during the aforementioned period, totaling 372 responses from a total of 1882 teachers eligible for the research. The Anxiety, Depression and Stress Scale (DASS-21), the Fear of COVID-19 Scale (FCV-19S) and the AUDIT instrument, which assesses alcohol use, were used. Bivariate analyzes and Poisson regression were performed. The prevalence ratio and its 95% confidence intervals (CI) were estimated. As a result, 52.7% of teachers were male and more than 60% were over 40 years old. Regarding lifestyle habits, 94.6% responded that they were not smokers and 73.9% used alcohol, with only 2.2% falling into the harmful use category. It was observed that 34.1% of teachers indicated characteristics of anxiety, 33.6% of stress and 39.2% of depression. Teachers with children had a 22% lower prevalence of depression than those who did not, with p=0.012; PR 0.78 and CI (0.64-0.94). Those who responded that they felt more afraid of COVID-19 had a higher prevalence of stress (29%) with p=0.002; PR 1.29 and CI (1.09-1.51) and a higher prevalence of depression (21%) with p =0.027; PR 1.21 and CI (1.02-1.44). Levels of anxiety, stress and depression influenced each other's prevalence. As the intensity of one of them increased, the prevalence of the others also increased. Higher education institutions must adopt strategies to prevent mental illness among teachers, contributing to quality education.